Estudo da produção de pectinase por fermentação em estado sólido utilizando pedúnculo de caju como substrato - Santos, Sharline Florentino de Melo (2007)
Pectinolytic enzymes, or simply pectinases, are complex enzymes that degrade pectic polymers. They have many uses, such as fruit juice extraction and purification, textile fiber treatment and vegetal oil extraction. The aim of this work was to study the kinetics of pectinases production by solid-state fermentation, using dry cashew apple residue as substrate and the microorganism Aspergillus niger CCT 0916. The influence of the initial medium moisture and medium supplementation with a source of nitrogen and phosphorus was evaluated using the factorial experimental planning and response surface methodology. Ammonia sulphate and potassium phosphate were used as nitrogen and phosphorus source, respectively. The variables time of contact (T) and ratio volume solvent/fermented medium (RZ), in systems with and without agitation, were evaluated in order to study the best extraction condition of the produced enzyme. Washed and unwashed cashew apple residues were tested as the growth medium. The unwashed residue was obtained by drying the residue after the extraction of the juice, while the washed residue was obtained by water washing 5 times using the proportion of 1 kg pulp/2 liters of water. Samples were taken every 12 hours for moisture content, pH, protein, reducing sugars, polygalacturonase activity (PG) and viscosity reduction. The physical-chemical composition of the residues had different sugar and pectin levels. For the unwashed residue, the peak activity was reached with 40% of initial moisture content, 1% of nitrogen supplementation without phosphorus addition after 30 hours of process. These conditions led to 16 U/g of PG activity and 82% of viscosity reduction. The calculated models reached similar values to the experimental ones in the same process conditions: 15.55 U/g of PG and 79.57% of viscosity eduction. Similarly, the greatest enzyme production for washed residue was reached with 40% initial moisture content, 1% nitrogen supplementation without phosphorus addition after 22 hours of cultivation. In this condition it was obtained polygalacturonase activity of 9.84 U/g and viscosity reduction of 81.36%. These values are close to experimental values that were of 10.1 U/g and 81%, respectively. The conditions that led to the best PG activity results was the agitated one and the best extraction condition was obtained with 100 minutes of solvent/medium contact and RZ of 5 (mL/g)